2019
DOI: 10.3390/molecules24122241
|View full text |Cite
|
Sign up to set email alerts
|

Set-Up and Validation of a High Throughput Screening Method for Human Monoacylglycerol Lipase (MAGL) Based on a New Red Fluorescent Probe

Abstract: Monoacylglycerol lipase (MAGL) is a serine hydrolase that has a key regulatory role in controlling the levels of 2-arachidonoylglycerol (2-AG), the main signaling molecule in the endocannabinoid system. Identification of selective modulators of MAGL enables both to provide new tools for investigating pathophysiological roles of 2-AG, and to discover new lead compounds for drug design. The development of sensitive and reliable methods is crucial to evaluate this modulatory activity. In the current study, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…An optimal HTS assay for changes in NAPE-PLD activity requires high reproducibility for replicate samples and sufficient dynamic range to reliably detect activators and inhibitors. Fluorogenic lipid substrates have been previously used successfully in HTS assays for modulators of lipase activity (38)(39). PED-A1 is a quenched fluorogenic NAPE analog that has previously been used to measure phospholipase A1 (PLA 1) activity in vitro and in tissue samples (40).…”
Section: Resultsmentioning
confidence: 99%
“…An optimal HTS assay for changes in NAPE-PLD activity requires high reproducibility for replicate samples and sufficient dynamic range to reliably detect activators and inhibitors. Fluorogenic lipid substrates have been previously used successfully in HTS assays for modulators of lipase activity (38)(39). PED-A1 is a quenched fluorogenic NAPE analog that has previously been used to measure phospholipase A1 (PLA 1) activity in vitro and in tissue samples (40).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of this acyl chain derives from our previous studies [ 31 , 32 , 33 , 34 , 35 ], which have suggested medium-short chains as a versatile substrate of lipase and esterase activity evaluation, and it is also supported by the recent literature [ 18 ]. Indeed, in a rational design of a substrate for lipolytic activity evaluation, the alkyl chain length should be carefully evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, continuing our interest in lipase selective probe development [ 31 , 32 , 33 , 34 , 35 ] suitable for in vitro and in vivo assays, we investigated a group of phenoxy-1,2-dioxetane luminophores, 2 – 4 , carrying an octanoyl chain as a triggerable substrate. The enzymatic cleavage of these phenoxy-dioxetane luminophores generates a direct chemiluminescence emission which is strongly dependent on the lipase activity.…”
Section: Introductionmentioning
confidence: 99%
“…uronium hexafluorophosphate (COMU) in the presence of diisopropylethylamine (DIPEA), or the activation of the acidic moiety passing through chlorine using oxalylchloride, were assessed. At first, COMU, a molecule of a third-generation uronium-type coupling previously used for the synthesis of other EC and NAEs or their derivatives [39][40][41][42][43], was assessed for arachidonate ester placement in the sn-2 position. Unfortunately, this procedure gave low yields (<40%) associated with long reaction times (>24 h).…”
Section: Resultsmentioning
confidence: 99%